Cover of night - Howard, Linda, 1950- (Ballantine, 2006)
In the charming rural town of Trail Stop, Idaho, accessible to the outside world by only a single road, young widow Cate Nightingale lives peacefully with her four-year-old twin boys, running a bed-and-breakfast. Though the overnight guests are few and far between--occasional hunters and lake fishermen--Cate always manages to make ends meet with the help of the local jack-of-all-trades, Calvin Harris, who can handle everything from carpentry to plumbing. But Calvin is not what he seems, and Cate's luck is about to run out.